Aghayan as a Dialectologist - HANANYAN, GAGHTUHI (Bulletin of Yerevan University B: Philology, 2021)
Dialectological research is an essential part of E. Aghayan’s scientific legacy. His monograph entitled ’’The Dialect of Meghri’’ is one of the most valuable studies of this kind. E. Aghayan’s works on the role of dialects in the development of the national language, the differentiation of Old Armenian dialects, the interrelation between Classical Armenian (Grabar) and Modern Armenian dialects, their origin and the problems of thier development are really invaluable. E. Aghayan gave a high priority to the inclusion of dialectal material in historical-comparative studies, highlighting the importance of Indo-European archaisms in Armenian dialects. Relying on the sound changes that occur in different layers of genetic lexicon, E. Aghayan defined the relative chronology of their modifications. E. Aghayan’s dialectological research provides rich data for further studies in Armenology.